Round-Tripping Foreign Direct Investment in the People's Republic of China: Scale, Causes and Implications - Xiao Geng (Asian Development Bank Institute (ADBI), 2004)
It is well known that much of the recorded foreign direct investment (FDI) to the People's Republic of China is financed by domestically generated funds that leave the country to return as `roundtripping' FDI. This paper provides one of the very few estimates of the magnitude of this form of FDI and suggests it is most likely around 40% of recorded flows. The author argues that conceptually FDI to an economy is linked with its capacity to generate new capital, so that FDI to the East Asian region cannot be seen as a zero-sum game, where the gain of one country is at the expense of another. Motives for round-tripping in the case of PRC are explored and it is suggested that these extend beyond the receipt of tax breaks and also encompass efficiency concerns. To estimate the scale of round-tripping the paper compares FDI statistics from the country of export with official PRC data for FDI from the exporting country. The discrepancy will be due in part to a normal statistical reporting error and in part to round-tripping. Systematic adjustments are made to separate the two components. The resulting estimates cannot be precise and are given as a range, but they indicate the very large scale of round-tripping FDI.
hdl:11540/4165
Keywords: 330; Auslandsinvestition; Kapitalmobilität; Kapitalflucht; China